ANALISIS RETORIKA TAHAJUL AL-ARIF TERHADAP SURAH AL ANBIYA AYAT 43-44 - Zakiah Mardiah Nasution; Tengku Sinar Marwanda; Predy Ady Ray Ritonga; Harun Al-Rasyid (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The purpose of this article is to discuss the rhetorical aspects of the verses of the Qur'an and analyze the quality of the meaning it has. This article uses a library research method with an inductive analysis approach that focuses on the meaning of the verses that provide additional rhetorical meaning that cannot be imitated. The results of the study explain that the rhetoric of the Qur'an has a very vital role in studying and examining the meaning of verses in the Qur'an. This is intended to reveal the quality of the cognitive meaning of the rhetoric of the Qur'an which is a source of linguistic discourse. Through understanding the rhetoric of the Qur'an, readers not only use it as the art of understanding the meaning of the verses of the Qur'an or convincing others but more than that as a science of language logic, philosophy, law and also religion and scientific argumentation in communication.